The effect of music classes conducted in northern cypriot schools with the kodály approach on the musical development of students: A pilot study - ÇOBAN, SİBEL (My University, 2023)
© The Author(s) 2023.The purpose of this research is to examine the effects of music classes conducted with the Kodály approach on the musical development of students. The research was carried out with the mixed method embedded design. The quantitative dimension of the research was carried out with the pre-test post-test control group experimental design, whereas, the case study comprises the qualitative dimension. The study group consisted of 24 experimental and 21 control group students. A lesson observation form, an aural skills test and an interview form were used to collect data in the study. The quantitative data was analyzed with SPSS 24.0, whereas the qualitative data was analyzed using the content analysis method. It was determined that the experimental group students were more successful than the control group students in their musical, rhythmic and melodic knowledge and skills. In addition, it is understood that the students found the classes conducted with the Kodály approach entertaining and instructive, and that the education in these classes was more comprehensible and more lasting with the use of Turkish Cypriot folk songs as a tool in music education in Northern Cypriot schools.
Keywords: Sosyal ve Beşeri Bilimler; Dil ve Edebiyat; Sanat; Müzik; Social Sciences and Humanities; Philology; Art; Music; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; MÜZİK; EDEBİYAT; SANAT; Arts & Humanities (AHCI); ARTS & HUMANITIES; MUSIC; LITERATURE; ART; Görsel Sanatlar ve Gösteri Sanatları; Sosyal Bilimler ve Beşeri Bilimler; Edebiyat ve Edebiyat Teorisi; Visual Arts and Performing Arts; Social Sciences & Humanities; Literature and Literary Theory; kodály approach; music education; musical development; rhythmic/melodic skills